IDENTIFIKASI SENYAWA METABOLIT SEKUNDER EKSTRAK ETANOL DAUN PECUT KUDA (Stachytarpheta jamaicensis L) MENGGUNAKAN GC-MS - Sukarti; Ilmiati Illing; Firka Rustam (Cokroaminoto Journal of Chemical Science)
This study aims to determine the types of secondary metabolites contained in the ethanol extract of the leaves of Pecut Kuda (Stachytarpetha jamaicensis L) using GC-MS. This research was started by maceration on samples in the form of simplicia powder for 3x24 hours using 96% ethanol as solvent to remove the active compound content in Pecut Kuda leaves. The next step is to identify secondary metabolites using GC-MS. The results of the identification of secondary metabolites in GC-MS showed that the active compounds in the ethanol extract of Pecut Kuda leaves were Linolenic acid, Neophytadiene, Butyl 9,12,15-octadecatrionoate, Hexadecanoic acid, Cyclopenta (c) pyran-4-carboxylic acid. , and Camphene. These active compounds have functions as antioxidants, anti-inflammatory, antimicrobial, antibiotic and free radical scavengers in wound healing